DNA and heparin chaperone the refolding of purified recombinant replication protein A subunit 1 from Leishmania amazonensis - Lira, C. B. B. [UNESP]; Gui, K. E.; Perez, A. M. [UNESP]; da Silveira, R. C. V. [UNESP]; Gava, L. M.; Ramos, C. H. I.; Cano, M. I. N. [UNESP] (Elsevier B.V., 2009)
Replication protein A (RPA) is a single-stranded DNA-binding protein that has been implicated in DNA metabolism and telomere maintenance. Subunit 1 of RPA from Leishmania amazonensis (LaRPA-1) has previously been affinity-purified oil a column containing a G-rich telomeric DNA. LaRPA-1 binds and co-localizes with parasite telomeres in vivo. Here we describe the purification and characterization of native recombinant LaRPA-1 (rLaRPA-1). The protein was initially re-solubilized from inclusion bodies by using urea. After dialysis, rLaRPA-1 was soluble but contaminated with DNA, which was removed by an anion-exchange chromatography of the protein solubilized ill Urea. However, rLaRPA-1 precipitated after dialysis to remove urea. To investigate whether the contaminating DNA was involved in chaperoning the refolding of rLaRPA-1, salmon sperm DNA or heparin was added to the solution before dialysis. The addition of either of these Substances prevented the precipitation of rLaRPA-1. The resulting rLaRPA-1 was soluble, correctly folded, and able to bind telomeric DNA. This is the first report showing the characterization of rLaRPA1 and of the importance of additives in chaperoning the refolding of this protein. The availability of rLaRPA-1 should be helpful in assessing the importance of this protein as a potential drug target. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Replication protein A Subunit 1; Leishmania amazonensis; Telomere-binding protein; Recombinant protein refolding; Heparin; spectroscopic analysis